Renal Tubular Cell Mitochondrial Dysfunction Occurs Despite Preserved Renal Oxygen Delivery in Experimental Septic Acute Kidney Injury. Issue 4 (April 2018) - Arulkumaran, Nishkantha; Pollen, Sean; Greco, Elisabetta; Courtneidge, Holly; Hall, Andrew M.; Duchen, Michael R.; Tam, Frederick W. K.; Unwin, Robert J.; Singer, Mervyn
Abstract : Objective: To explain the paradigm of significant renal functional impairment despite preserved hemodynamics and histology in sepsis-induced acute kidney injury. Design: Prospective observational animal study. Setting: University research laboratory. Subjects: Male Wistar rats. Intervention: Using a fluid-resuscitated sublethal rat model of fecal peritonitis, changes in renal function were characterized in relation to global and renal hemodynamics, and histology at 6 and 24 hours ( n = 6–10). Sham-operated animals were used as comparison ( n = 8). Tubular cell mitochondrial function was assessed using multiphoton confocal imaging of live kidney slices incubated in septic serum. Measurements and Main Results: By 24 hours, serum creatinine was significantly elevated with a concurrent decrease in renal lactate clearance in septic animals compared with sham-operated and 6-hour septic animals. Renal uncoupling protein-2 was elevated in septic animals at 24 hours although tubular cell injury was minimal and mitochondrial ultrastructure in renal proximal tubular cells preserved. There was no significant change in global or renal hemodynamics and oxygen delivery/consumption between sham-operated and septic animals at both 6- and 24-hour timepoints. In the live kidney slice model, mitochondrial dysfunction was seen in proximal tubular epithelial cells incubated with septic serum with increased production of reactive oxygen species, and decreases in nicotinamide adenine dinucleotide and mitochondrial membrane potential. These effects were prevented by coincubation with the reactive oxygen species scavenger, 4-hydroxy-2, 2, 6, 6-tetramethyl-piperidin-1-oxyl. Conclusions: Renal dysfunction in sepsis occurs independently of hemodynamic instability or structural damage. Mitochondrial dysfunction mediated by circulating mediators that induce local oxidative stress may represent an important pathophysiologic mechanism. Abstract : Supplemental Digital Content is available in the text.